Estimating energy intensity interactions among world's regions, world GDP per capita and world energy price - Mustafa Akal (Economic and Environmental Studies (E&ES), 2014)
This study attempts to predict energy intensities of world's regions, the world gross domestic product per capita and the world energy price via developing VAR (2) model. Whether causalities exist between groups of variables are tested by proceeding Granger Wald Test to structure a VAR model inductively. There exist significant causal and dynamical interactions among the variables, implying that regions' energy use affect each others' energy intensity (adversely efficiency), each of which is also found interacting with the world gross domestic product per capita and world unit energy price at different magnitudes. Additional energy uses of regions per US 1000 output mostly lead to per capita world gross domestic product and energy price up except for Sub-Saharan Africa. Increases in the last year's world gross domestic product per capita mostly cause inefficiency, however, increases in the last two years' world gross domestic product per capita mostly improve efficiency of world regions. Except for South Asia, an increase in world energy price does not improve energy use efficiency of the world's regions for the period of 1971 - 2009.
Keywords: 330; World's regions; energy intensity; VAR model; interaction